Scorpion venom peptides: Molecular diversity, structural characteristics, and therapeutic use from channelopathies to viral infections and cancers - Zhiqiang Xia; Dangui He; Yingliang Wu; Hang Fai Kwok; Zhijian Cao (Elsevier, 2023)
Animal venom is an important evolutionary innovation in nature. As one of the most representative animal venoms, scorpion venom contains an extremely diverse set of bioactive peptides. Scorpion venom peptides not only are 'poisons' that immobilize, paralyze, kill, or dissolve preys but also become important candidates for drug development and design. Here, the review focuses on the molecular diversity of scorpion venom peptides, their typical structural characteristics, and their multiple therapeutic or pharmaceutical applications in channelopathies, viral infections and cancers. Especially, the group of scorpion toxin TRPTx targeting transient receptor potential (TRP) channels is systematically summarized and worthy of attention because TRP channels play a crucial role in the regulation of homeostasis and the occurrence of diseases in human. We also further establish the potential relationship between the molecular characteristics and functional applications of scorpion venom peptides to provide a research basis for modern drug development and clinical utilization of scorpion venom resources.